2000
DOI: 10.1037/0097-7403.26.4.439
|View full text |Cite
|
Sign up to set email alerts
|

Geometric rule learning by Clark's nutcrackers (Nucifraga columbiana).

Abstract: Clark's nutcrackers (Nucifraga columbiana) were trained to search in a location defined by its geometric relationship to 2 landmarks. Two groups were trained to search at different points along the line connecting the landmarks, and 2 groups were trained to find the 3rd point of a triangle, on the basis of either direction or distance from the landmarks. All groups learned and transferred to new interlandmark distances. However, the constant-distance group learned more slowly, searched less accurately, and sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
92
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(109 citation statements)
references
References 19 publications
12
92
5
Order By: Relevance
“…It appears that pigeons had more difficulty localizing the midpoint between the landmarks than determining how far from the landmark array to search. In contrast, Kamil and Jones (2000) found no significant differences between axes in either the constant-bearing or the constant-distance group of nutcrackers.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…It appears that pigeons had more difficulty localizing the midpoint between the landmarks than determining how far from the landmark array to search. In contrast, Kamil and Jones (2000) found no significant differences between axes in either the constant-bearing or the constant-distance group of nutcrackers.…”
Section: Discussioncontrasting
confidence: 71%
“…By contrast, nutcrackers trained in the constant-bearing condition showed excellent transfer to both the interpolated and extrapolated novel interlandmark distances (Kamil & Jones, 2000). Nutcrackers in the constant-distance condition showed good transfer to interpolated distances but an increase in error for the extrap- olated distances.…”
Section: Discussionmentioning
confidence: 75%
“…For example, food-storing birds and rats use flexible hierarchies of spatial learning, the expression of which changes with circumstances and previous experience (e.g., Brodbeck, 1994;Kamil & Jones, 2000;Roche & Timberlake, 1998;Shettleworth & Sutton, 2005). Observations of free-ranging rats also support the operation of multiple spatial mechanisms in establishing and using trails connecting burrows and feeding areas (Calhoun, 1962;Leonard & McNaughton, 1990).…”
mentioning
confidence: 99%
“…The birds learned the task readily and searched extremely accurately when tested with new interlandmark distances. Follow-up studies demonstrated that nutcrackers could learn other geometrical rules (Kamil and Jones, 2000), including the use of relative bearings Jones and Kamil, 2001). Comparative studies found that nutcrackers performed these tasks much more accurately than pigeons (Jones et al, 2002;Spetch et al, 2003).…”
Section: Landmarks and The Coding Of Spatial Locationsmentioning
confidence: 99%